The impact of gender differences on the roles of the atherogenic index of plasma and triglyceride-glucose index in predicting moderate to severe coronary artery calcification - Kaynak, Çağdaş; Aslan, Muzaffer; Yazıcı, Selim; Okşen, Dogaç (The European Research Journal, 2025)
Objective: This study aimed to evaluate the association of the triglyceride-glucose (TyG) index and the atherogenic index of plasma (AIP) with moderate-to-severe coronary artery calcium score (CACS), with a particular focus on gender differences. Given the gender-specific variations in the development of coronary artery calcification, tailored diagnostic approaches are required. Methods: In this retrospective, single-center study, 246 consecutive patients aged 25-77 years who underwent 128-slice coronary computed tomography angiography (CCTA) for coronary artery disease screening between June 2024 and January 2025 were analyzed. Patients were categorized into three groups according to their CACS: Group 1 (CACS=0), Group 2 (CACS=1-99), and Group 3 (CACS≥100). Demographic characteristics and medical histories were recorded. Biochemical parameters, lipid panel, and hemogram values were analyzed from venous blood samples collected after 12 hours of fasting. Multivariate logistic regression analyses were performed to identify independent predictors of moderate-to-severe CACS in both genders. Results: In women, advanced age (odds ratio [OR]=1.126; 95% confidence interval [CI]: 1.031–1.136; P<0.001), elevated triglyceride levels (OR=0.964; 95%CI:0.937–0.992; P=0.011), and a higher TyG index (OR=35.317;95%CI:6.328–187.356; P=0.002) were independently associated with moderate-to-severe CACS. In men, advanced age (OR=1.083; 95% CI:1.007–1.165; P=0.032), severe coronary artery stenosis (OR=12.298; 95% CI: 1.451–104.208; P=0.021), and smoking (OR=8.771; 95%CI: 1.810-42.501; P=0.007) were independent predictors. AIP was not identified as an independent predictor of moderate-to-severe CACS in either gender. Conclusions: Advanced age was independently associated with CACS in both genders. The TyG index was a significant predictor of moderate-to-severe CACS in women, while traditional risk factors, such as smoking and severe coronary artery stenosis, were more relevant in men. AIP was not an independent predictor of moderate-to-severe CACS in either gender.